Spatial quantile regression in analysis of healthy life years in the European Union countries - Grażyna Trzpiot; Agnieszka Orwat-Acedańska (Comparative Economic Research. Central and Eastern Europe, 2016)
The paper investigates the impact of the selected factors on the healthy life years of men and women in the EU countries. The multiple quantile spatial autoregression models are used in order to account for substantial differences in the healthy life years and life quality across the EU members. Quantile regression allows studying dependencies between variables in different quantiles of the response distribution. Moreover, this statistical tool is robust against violations of the classical regression assumption about the distribution of the error term. Parameters of the models were estimated using instrumental variable method (Kim, Muller 2004), whereas the confidence intervals and p-values were bootstrapped.
Keywords: 330; quantile regression; multiple spatial quantile autoregression; spatial analysis; healthy life years